The Effect of Wrist Flexibility Exercise Using a Bottle on the Ability of Smash Badminton at the Extracurricular of SMK Negeri 2 Palembang - Simanjuntak, Jetri Jogi; Lian, Bukman; Akhbar, M Taheri (Journal of Social Work and Science Education, 2023)
The purpose of this study was to determine whether there was an effect of wrist flexibility training using a bottle on the ability to smash in badminton games for extracurricular students at SMK Negeri 2 Palembang. The research method used is the one group pretest-posttest experimental method. The data source for this study were 20 students who took part in badminton extracurricular activities at SMK Negeri 2 Palembang. The data analysis technique uses the t-test formula. The results showed that wrist flexibility exercises using a bottle had an influence on the ability to hit badminton smash on extracurricular students at SMK Negeri 2 Palembang with results showing t-count = 2.638 > t-table = 2.093. So that the exercise of flexing the wrist using a bottle has a significant effect on the ability to smash in a badminton game.